International journal of knowledge society research (IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2010)
The International Journal of Knowledge Society Research (IJKSR) establishes an effective channel of communication between, academic and research institutions, policy makers, government agencies, and persons concerned with the analysis of various aspects of the knowledge society. This journal anchors government policies the characteristics of the emerging knowledge intensive economy and social environment. IJKSR investigates key priorities of the knowledge society in terms of critical aspects of human life (e.g. health, education, culture, science, business, etc.).